Pemikiran Ekonomi Islam di Indonesia - Wulan Ariby; Naila Deswita; Isma Awaliyah; Ahmad Wahyudi Zein (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2024)
Islamic economics in Indonesia has significant potential to build a just and sustainable economic system. This research aims to examine the development of Islamic economics in Indonesia, with a focus on the challenges and opportunities faced. Using literature analysis methods, this research explores the progress of the Islamic finance sector, the influence of the thoughts of figures such as Monzer Kahf and M. Umer Chapra, as well as the application of the main principles of Islamic economics. The results of the study show that although the Islamic economic sector has developed rapidly since the founding of Bank Muamalat in 1992, there are still a number of obstacles, such as low public understanding of sharia finance, regulations that are not yet optimal, and a lack of experts in this field. However, great opportunities are seen in the development of the halal industrial sector, integration of sharia- based financial technology, and government policy support. The main principles of Islamic economics, such as the oneness of God (tauhid), social justice, and the prohibition of usury, are important guidelines in facing modern economic challenges. The thoughts of figures such as Kahf and Chapra strengthen Islamic economic practices, especially in sharia financial management and fair distribution of wealth. With policy reform, improved education, and innovation in sharia financial products, the Islamic economy in Indonesia can develop into one of the main pillars of inclusive economic development and support the achievement of sustainable development goals (SDGs).